ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN OMSET PENJUALAN PADA KEDAI TENTANG KITA MINUMAN COKELAT KEKINIAN KOTA SORONG - Mitri Tanti Selong; Ade Andriani Renouw; Andrey Maryen (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the marketing strategy in increasing sales turnover at the About Us Chocolate Drink Shop, Sorong City. The type of research conducted in this study was a qualitative descriptive analysis. This type of research is qualitative research with a SWOT analysis approach About Us Contemporary Chocolate Drinks in Sorong City consisting of strengths, namely price can be determined by yourself, strategic location, and availability of large parking lots. While the weaknesses are the unavailability of snacks, the lack of menu variants offered, and the promotions that have been carried out have not been fully maximized. Then opportunity (opportunity), namely the loyalty of loyal customers who visit (a good relationship), different variants of chocolate drinks. While the threat is that there are many new competitors and similar to the About Us Contemporary Chocolate Drinks shop, Sorong city. as a means to carry out promotions, and provide facilities in the form of Wifi and non-smoking areas so that consumers feel more comfortable while in the shop.